Improving Self-Regulated Learning with Self-Management Tool. - Abdullah, Melissa Ng Lee Yen (Penerbit USM, 2013)
Self-regulated learning is recognized as one of the most essential skills that students should possess in this information age. Nevertheless, most students are accustomed to the conventional teacher-centered way of learning, thus, they are not competent at self-regulated learning. A Self-Management Tool was developed to guide and enhance students' usage of self-regulated learning strategies. The tool comprises three components; Information-Management Tool, Personal-Management Tool and a Teacher's Manual. A quasi-experimental study was conducted to test its effectiveness and the details of this.